Analisis Pengaruh Harga dan Kualitas Produk terhadap Kepuasan Konsumen Produk Kecantikan Wardah di Surabaya - Auliatus Sholihah; Handy Aribowo (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
The purpose of this study is to determine the influence of price and product quality on consumer satisfaction of Wardah beauty products in Surabaya. The data collection technique in this study is using the probability sampling method with a simple random sampling technique by taking random samples. The sample in this study used 100 respondents who were users of Wardah beauty products in Surabaya. The result of this study is that price has an influence on consumer satisfaction, as evidenced by the results of a partial research test (T) where the price variable has a sign value. 0.000 < 0,05, and the t-value is 17,482 > 1,984. And product quality has an influence on consumer satisfaction, as evidenced by the results of the Partial (T) research test, where the Product Quality variable has a significant value. 0.000 < 0.05, and the t-value is calculated 17,366 > 1,984. Meanwhile, in the results of the simultaneous research test (F), the price and quality of the product have a sign value. 0.000 < 0.05 and the f-value is calculated 186,267 > 3,089, so it can be concluded in this study that price and product quality simultaneously have a positive effect on consumer satisfaction.